Observation of Rapid Exciton–Exciton Annihilation in Monolayer Molybdenum Disulfide - Sun, Dezheng; Rao, Yi; Reider, Georg A; Chen, Gugang; You, Yumeng; Brézin, Louis; Harutyunyan, Avetik R; Heinz, Tony F (Nano letters, 2014)
Monolayer MoS2 is a direct-gap two-dimensional semiconductor that exhibits strong electron–hole interactions, leading to the formation of stable excitons and trions. Here we report the existence of efficient exciton–exciton annihilation, a four-body interaction, in this material. Exciton–exciton annihilation was identified experimentally in ultrafast transient absorption measurements through the emergence of a decay channel varying quadratically with exciton density. The rate of exciton–exciton annihilation was determined to be (4.3 ± 1.1) × 10–2 cm2/s at room temperature.